Development of Interactive Multimedia Based on Contextual Approaches on Natural Resource Conservation Materials - Ni Wayan Sri Sukma Rahayu; A. A. Gede Agung (Universitas Pendidikan Ganesha, 2022)
This development study was carried out because the media used by the teacher was less communicative, interesting and varied, thus making students easily bored and bored. The development goal is to create interactive multimedia based on a contextual approach to natural resource conservation material for science lessons. This study uses the ADDIE model. The research subjects included learning content experts, learning design experts, learning media experts and 12 students. Methods of data collection using a questionnaire. Data analysis used descriptive quantitative data analysis techniques. Results review learning content experts show very good qualifications, Results review learning design experts showed good qualifications. Results review learning media experts showed very good qualifications. The results of individual trials showed very good qualifications, and the results of small group trials showed very good qualifications. So interactive multimedia is suitable for use in science learning in fourth grade primary school. The implication of this research is that the use of interactive multimedia can make students not easily bored and bored.